2022
DOI: 10.1021/acsapm.1c01568
|View full text |Cite
|
Sign up to set email alerts
|

Thermally Controlled Acceleration of Epoxy Resin Curing through Polymer-Bound Imidazole Derivatives with High Latency

Abstract: Imidazole-containing polymeric accelerators were synthesized through free-radical polymerization and applied in the curing of diglycidyl ether of bisphenol A resin with the hardener dicyandiamide. Reactivity and storage stability were followed via differential scanning calorimetry, and an increased pot life was observed after incorporation into polymers. Depending on the employed monomers and composition, the compatibility with epoxy resin was adjusted and the storage stability thereby improved, while a high r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…The possible reason is attributed to the presence of imidazole moiety. It has high reactivity under appropriate heating conditions, for instance, acting as a thermal initiator in the curing of epoxy resin 38 . Likewise, we speculated that the hydrogen atom of N‐imidazole group could capture some radicals generated during NR aging so as to further disrupt the degradation/crosslink reactions partly.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…The possible reason is attributed to the presence of imidazole moiety. It has high reactivity under appropriate heating conditions, for instance, acting as a thermal initiator in the curing of epoxy resin 38 . Likewise, we speculated that the hydrogen atom of N‐imidazole group could capture some radicals generated during NR aging so as to further disrupt the degradation/crosslink reactions partly.…”
Section: Resultsmentioning
confidence: 97%
“…It has high reactivity under appropriate heating conditions, for instance, acting as a thermal initiator in the curing of epoxy resin. 38 Likewise, we speculated that the hydrogen atom of N-imidazole group could capture some radicals generated during NR aging so as to further disrupt the degradation/crosslink reactions partly. In addition, the low thermal conductivity of porous ZIF-8 (the simulation result is 0.165 W/m K 39 ) was supposed to obstruct heat transfer and afford NR matrix with good thermal aging resistance.…”
Section: Thermo-oxidative Aging Resistance Of Nr Compositesmentioning
confidence: 99%
“…After raising the temperature from room temperature to 250 °C, only an exothermic peak was observed at 234.3 °C when no catalyst was applied . After DMAP, imidazole and 1,2-dimethylimidazole were applied, the exothermic peak obviously shifted to low temperature (208.8, 162.8, and 137.3 °C). It indicated that 1,2-dimethylimidazole seems to be the ideal catalyst to prepare biobased epoxy elastomers from Priamine 1074 and ESO under relatively mild reaction conditions.…”
Section: Resultsmentioning
confidence: 99%
“…[3,4] In materials science, crosslinking reactions are widely used in the preparation of gel materials, 3D DOI: 10.1002/marc.202300199 printing materials, and thermosetting resins, among others. [5][6][7][8][9][10][11][12][13][14][15] However, some crosslinking reactions, such as those based on nitrile chemistry, still face the challenge of harsh reaction conditions, which limit their application. [16,17] Enhancing the reactivity of nitrile is crucial for expanding the application of 3D crosslinking materials.…”
Section: Introductionmentioning
confidence: 99%